Homelessness, Housing First, and the Right to Housing—Confronting Right and Reality - Taylor, Owen (Human rights review, 2020)
The scale of homelessness in Europe throws a stark light on the right to housing that exists in many European states and in European and International Law. This disparity between legal right and the social reality of homelessness and housing precarity begs the question as to the efficacy of a rights-based approach to housing., This article examines the ‘enforceable’ right to housing in France, in place since 2007, to explore the efficacy of approaching a chronic lack of housing through justiciable rights. The lack of progress in over a decade of jurisprudence highlights the challenges posed to legal advocacy in this area, particularly when combined with a lack of political will. The article concludes by reflecting on alternative approaches, in which justiciable rights have played less of a role, stressing the need for political and financial commitment over legal rights.